Penyuluhan Pencegahan Dan Penanganan Penyakit Pada Ikan Lele (Clarias sp.) Di Desa Bua Kecamatan Batudaa Kabupaten Gorontalo - Hendrik David Julianus Borolla; Juliana Juliana (Politeknik Kampar, 2023)
Catfish is one of the leading commodities in Indonesia. Business development can be done from seed to consumption size. The main obstacle to cultivation tends to be the presence of pests and diseases that occur in catfish. Counseling was carried out in Bua village, Kec. Batudaa on December 18 2023 with the target of outreach being catfish cultivator groups. In catfish cultivation activities carried out by a group of farmers in Bua village, Kec. Batudaa failed due to lack of preparation and knowledge of catfish cultivation. The aim of this outreach is to provide knowledge to the public on how to handle and prevent disease in catfish. The results of the outreach were that the people of Bua village knew how to cultivate catfish properly and how to prevent and treat diseases in catfish.